Life Quality Assessment of Patients Suffering from Oral Cancer (Medical Forum Monthly, 2024)
Objective: This study was aimed to determine the patient’s own perception of quality of life (QL); that were under treatment for oral cancers. University of Washington Quality of Life Questionnaire (UW-QOL) 1 was used as a screening tool for this purpose.Study Design: Questionnaire based Cross Sectional Study.Place and Duration of Study: This study was conducted at Kiran hospital Karachi, (Karachi Institute of Radiotherapy and Nuclear Medicine) from March to August 2011.Materials and Methods: Thirty patients diagnosed with oral cancer that were coming for treatment at the Kiran hospital Karachi, (Karachi Institute of Radiotherapy and Nuclear Medicine) were included in the sample. No limitation of age or cancer stage was specified.Result: Data analysis with SPSS showed that majority of patient surveyed had pain that was controlled by medications; majority of patient felt significantly disfigured; had limited activities. Although activities were slowed down due to fatigue still patients managed to go out however enjoyable recreation was bounded for patients. Swallowing function showed variation from no change, complete liquid diet, soft diet to choking. However most patients could chew soft foods, majority of patient had difficulty with some words but their speech was understood on phone. Greater parts choose no issue regarding function and pain in shoulders. Almost half the patients had normal consistency of saliva, mood mostly unaffected and majority patient were not anxious about their tumour lesion. General health was better before development of cancer and was good in previous seven days. Over all mental health and spiritual health was outstanding and pain was the most important issue patient complained.Conclusion: This study emphasizes the importance of measuring quality of life of oral cancer patients. UW-QOL1 questionnaire was an effective screening tool for evaluating the different domains from each patient at an individual level.